Implementasi Manajemen Mutu Pendidik di SMP IT Al Mumtaz Pontianak - Hestari, Vivin; Wicaksono , Luhur; Mulyana, Mulyana; Millah, Roihatul (Universitas Muhammadiyah Surakarta, 2024)
The research aims to describe the planning of recruitment, selection, placement, reward, supervision, and supporting factors in the implementation of educational quality management at SMP IT Al Mumtaz Pontianak. The research takes the form of a qualitative approach with a case study design. There are four subjects aged 35-43 years old, consisting of 1 principal, 1 vice principal for curriculum, 1 treasurer, and 1 staff member of the foundation in the HR department. Data collection methods include observation, interviews, and documentation. Data analysis utilizes the interactive model by Miles and Huberman, which involves data collection, reduction, presentation, and conclusion. Data validity is ensured through source triangulation and technique triangulation. The main findings of the research are: (1) Planning (recruitment) is carried out in accordance with the stages, guided by quality management, and complies with the SIT educator standards, (2) Selection is done through administrative processes, interviews, and microteaching, (3) Placement is based on educational qualifications and competency as educators, (4) Rewards for educators meet school criteria in the form of direct and indirect monetary and material incentives, (5) Supervision is effectively conducted through routine agendas to report activity results and school budgets, (6) Supporting factors in the implementation of educational quality management include internal and external factors. In conclusion, educational quality management has been implemented at SMP IT Al Mumtaz Pontianak. The implications range from planning (recruitment), selection, placement, reward, supervision, and supporting factors in the implementation of quality management at SMP IT Al Mumtaz.